If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying h + c = 24 Reorder the terms: c + h = 24 Solving c + h = 24 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-1h' to each side of the equation. c + h + -1h = 24 + -1h Combine like terms: h + -1h = 0 c + 0 = 24 + -1h c = 24 + -1h Simplifying c = 24 + -1h
| -7x-6x=-2x | | 8x+2+74=180 | | 8/10-5/7 | | -4+3t=-12+13t | | 3x+1=3(3x+1)-5 | | 2/5d-6/5=30 | | =x(95-4x) | | 5-m=-11-5m | | 4z^-1/8(3z^7-z^-1/8) | | 2x^2+8x+3x+12=0 | | 4n+8-4n=14+6n | | (5a^6b^2-15a^3b^5)/(5a^5b^3) | | 56+x+6=180 | | 144=x+2+x+3 | | 3x+5y=65 | | 6-6n=-6-2n | | 7t-3=2(t+1)+2 | | 3x+4x-5=37 | | -5k+3k=-4k+2 | | 15x+20y=875 | | x+-3-3=-6 | | R(x)=x(95-4x) | | x^2+3x-127=0 | | 4+a-8a=-17 | | 80+95+x+38=180 | | n*6=24+n | | 13x-5x+6-2x= | | 7(-5x+5)=0 | | 90+90+128+x=180 | | 1-5x-2x=15 | | x^2+y^2+8x+4y= | | 15(3x+1)+20(3(3x+1))-5=875 |